Exogenous bamboo pyroligneous acid improves antioxidant capacity and primes defense responses of harvested apple fruit. (December 2020) - Liu, Xiaoyun; Li, Jiangkuo; Cui, Xiaomin; Ji, Dongchao; Xu, Yong; Chen, Tong; Tian, Shiping
Abstract: Quality deterioration and fungal pathogen infection always cause severe yield loss for fresh fruit at postharvest stage. Hence, safe and efficient measures are in great demand. In the present study, the efficacy of bamboo pyroligneous acid (BPA) for improving intrinsic antioxidant capacity and inducing defense responses of harvested apple fruit was assessed. BPA treatment (250 and 500 mL L −1 ) dramatically activated the activities of major enzymes in phenylpropanoid metabolic pathway and antioxidant enzymes, ameliorated free radical scavenging capacity, resulting in elevated total flavonoid and total phenolic contents. The lower malonaldehyde (MDA) content and H2 O2 level also indirectly reflected the antioxidant efficacy of BPA. Moreover, BPA (10, 20, 30 mL L −1 ) also significantly inhibited mycelial growth of Botrytis cinerea by inducing reactive oxygen species burst, leading to impairment in membrane integrity and cell vitality as well as leakages of cytoplasmic contents. Taken together, these findings demonstrated that BPA was effective for maintaining intrinsic quality of apple fruit and inhibiting gray mold, which may be promising for alleviating quality deterioration and controlling diseases caused by fungal pathogens. Highlights: Bamboo pyroligneous acid (BPA) ameliorated antioxidant capacity of harvested apple fruit. BPA activated phenylpropanoid metabolic pathway of harvested apple fruit. BPA inhibited mycelial growth and virulence of Botrytis cinerea . BPA impaired membrane integrity and caused cytoplasmic content leakage of Botrytis cinerea.